EARLY TREATMENT RESPONSE OF BREAST CANCER BRAIN METASTASES TO GAMMA KNIFE STEREOTACTIC RADIOSURGERY: EARLY RESPONSE OF BRAIN METASTASES TO GAMMA KNIFE - Jovanovic, Marija; Davidovic, Kristina; Petkovic, Ana; Seha, Biljana; Jeremic, Danilo; Milicevic, Mihailo; Bogdanovic, Ivan; Ilic, Rosanda (Medical Research, 2024)
Introduction: Brain metastases represent the most common intracranial malignancy in the adult population, while breast cancer represents the leading cause of brain metastases among women. The incidence of brain metastases has seen an increase in recent years due to improved therapeutic control of systemic disease and better diagnostic tools. Stereotactic radiosurgery (SRS) is used in patients with brain tumors to achieve local disease control, preserve the quality of life, and extend patient survival. The aim of this study was to evaluate the effects of SRS in patients with brain metastases from breast cancer through analysis of magnetic resonance imaging (MRI) parameters of the brain.Methods: Brain MRI was conducted in 30 adult female patients before and 3-6 months after SRS treatment. Radiological analysis was used to estimate lesion volumes before and after SRS.Results: Patients were categorized into 4 groups based on therapeutic response: 1 - complete response with loss of the lesion, 2 - partial response with more than 50% reduction in lesion volume, 3 - disease progression with more than 25% increase in lesion volume, 4 - stable disease if the patient did not display a partial response or disease progression. Following the SRS treatment, a statistically significant reduction in tumor volume was observed, indicating effective lesion size reduction.Conclusion: Radiological volumetric analysis of brain metastases after SRS showed a statistically significant reduction in lesion volume, demonstrating effective local disease control.
Keywords: brain metastases, breast cancer, stereotactic radiosurgery, magnetic resonance imaging